Acute Kidney Injury Post-cardiac Surgery in Infants and Children: A Single-Center Experience in a Developing Country - Aoun, Bilal; Daher, Ghadi Abu; Daou, Karim N.; Sanjad, Sami; Tamim, Hani; El Rassi, Issam; Arabi, Mariam; Sharara, Rana; Bitar, Fadi; Assy, Jana; Bulbul, Ziad; Degheili, Jad A.; et al. (Frontiers in Pediatrics, 2021)
Background: The incidence of acute kidney injury (AKI) in pediatric patients following cardiac surgery varies between 15 % and 64 %, with a mortality rate of 10-89 % among those requiring dialysis. This variation in the incidence and mortality of AKI across studies are due to the inconsistent definitions used for AKI. Methods: We evaluated the incidence of AKI using the KDIGO criteria in 150 infants and children undergoing cardiac surgeries between 2015 and 2017. Post operatively, all patients were admitted to the Pediatric Intensive Care Unit (PICU) at a tertiary care center in a developing country. This is a retrospective chart review in which data collected included: age, gender, type of heart disease, prior cardiac surgeries, RACHS-1 category, and pre- and post-operative creatinine levels. Neonates were not included in this study. Results: Six percent of the studied patients were below one year of age, 84%, 1-10 years and 10%, 10-18 years. Fourteen patients (9.3%) developed AKI. Patients with cyanotic heart disease were more prone to develop AKI (78%) compared to those with noncyanotic heart disease (44%). Children with AKI had a higher length of stay in PICU, 2.56 ± 1.44 vs 4 ± 2.66 (p- 0.02). Serum lactic acid was higher in patients who developed AKI with a mean value of 6.8 ± 6.9 vs. 2.85 ± 1.55 in the non-AKI group (p- 0.03). Lower hemoglobin levels and hyperlactic acidemia were significantly more prevalent in the AKI group. There were 5 death in this series (3.3%) and 4 of those (80%) were in the AKI group. Conclusions: Using KDIGO criteria, the incidence of AKI in infants and children following cardiac surgery was 9.3%. This is slightly lower than previously published studies which range between 15% and 64%. Children with cyanotic cardiac disease, hyperlactic acidemia and anemia were more prone to develop AKI. Identifying patients at risk might help in decreasing the risk of postoperative AKI.